Shareholders’ perception of management communications in annual general meetings: narrative or not? - Oskouei, Malektaj Maleki; Nikoomaram, Hashem; Roodposhti, Freydoon Rahnama (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
This study investigates management communications in annual general meetings (AGMs) from a narrative perspective. This study evaluates the effective elements of AGMs from the shareholder’s viewpoint. According to the theoretical framework, the authors developed a conceptual model and extracted the suggested narrative model for the first time. The shareholder’s perception was measured through a questionnaire survey containing three sections – narrative, audience, and narrator – with 32 indicators from 151 shareholders measuring shareholders’ opinions about AGMs in Iran. The results indicate that although shareholders do not consider the AGM communications made by management board as a narrative, they obtain relevant information with a logical flow in AGMs, and believe that these relations are useful. The characteristics of the management board impact on the persuasiveness of their communications. The results supported the mediating effect of AGM communication between managers and shareholders
Argumenta Oeconomica, 2020, Nr 2 (45), s. 77-103
Keywords: AGM; narratives; organization ritual; shareholders; PLS-SEM